2002
DOI: 10.1099/00221287-148-8-2591
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of novel small RNAs in the aspS–yrvM intergenic region of the Bacillus subtilis genome

Abstract: A novel RNA species was isolated from Bacillus subtilis, and its sequence was determined and mapped to its genetic position. This RNA was termed BS190 RNA from the length of its mature form (190 nt), and the gene encoding it is located within the aspS-yrvM intergenic region of the B. subtilis genome. Northern blotting revealed that the novel RNA species is transcribed in vegetative cells as a larger precursor (BS201 RNA, 201 nt). After transcription, the 5' end of the precursor is processed to generate the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 36 publications
(28 reference statements)
1
28
0
Order By: Relevance
“…1E] indicated that the 5'-extended version is the primary transcript carrying a 5'-triphosphate protecting the RNA from 5'-exonucleolytic degradation. These findings are consistent with 6S-1 RNA being transcribed as a 201 nt long 5'-precursor that is processed to its mature form (190 nt), 16 in line with the appearance of two bands in the northern blot (Fig. 1B).…”
supporting
confidence: 76%
See 3 more Smart Citations
“…1E] indicated that the 5'-extended version is the primary transcript carrying a 5'-triphosphate protecting the RNA from 5'-exonucleolytic degradation. These findings are consistent with 6S-1 RNA being transcribed as a 201 nt long 5'-precursor that is processed to its mature form (190 nt), 16 in line with the appearance of two bands in the northern blot (Fig. 1B).…”
supporting
confidence: 76%
“…1B), in line with previous observations. 6,15 As reported before, 6,16 6S-1 RNA occurs as a 201-nt precursor form (p6S-1) and a 190-nt mature RNA (m6S-1) in B. subtilis cells (Fig. 1B).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…At their discovery, the genes for the two ncRNAs were termed bsrA and bsrB Suzuma et al 2002), but their nature as 6S RNAs was only unveiled in a later study by the Wassarman group (Trotochaud and Wassarman 2005). Both RNAs were shown to coimmunoprecipitate with the σ A housekeeping RNAP holoenzyme using antibodies against σ A or the core subunit α (Trotochaud and Wassarman 2005).…”
Section: Introductionmentioning
confidence: 99%